Pengaruh Pemanfaatan TikTok terhadap Exposure Digital dan Brand Awareness pada UMKM Indonesia - Diana Novita; Hanifah Hanifah (Jurnal Minfo Polgan, 2026)
The rapid advancement of digital communication technology has significantly transformed contemporary marketing strategies toward the utilization of visually oriented social media platforms. Social media enables organizations and individuals to engage audiences interactively while creating value through user-generated content and digital participation (Kaplan & Haenlein, 2019). One of the fastest-growing platforms is TikTok, which facilitates algorithm-driven content distribution through personalized recommendation systems. Unlike traditional platforms that rely heavily on follower counts, TikTok allows content to reach wider audiences organically based on engagement performance and viewing behavior (Dwivedi et al., 2021). This study aims to analyze the influence of TikTok utilization on increasing digital exposure and its subsequent impact on brand awareness. The research employed a quantitative approach using an explanatory research design. Data were collected through structured questionnaires distributed to 150 respondents consisting of small and medium enterprise (SME) owners and active TikTok content creators. Data analysis was conducted using IBM SPSS Statistics, including validity testing, reliability testing, linear regression analysis, and hypothesis testing (Hair et al., 2019). The results indicate that the intensity of TikTok usage significantly influences digital exposure (β = 0.742; Sig. 0.000). Furthermore, digital exposure has a positive and significant effect on brand awareness (β = 0.691; Sig. 0.000). These findings support previous research stating that increased online exposure enhances consumer recognition and strengthens brand positioning (Kotler & Keller, 2016; Ashley & Tuten, 2015). Overall, the study confirms that TikTok functions as a strategic digital marketing medium capable of improving online visibility and reinforcing brand identity within the modern digital ecosystem.